2016
DOI: 10.1186/s40409-016-0065-8
|View full text |Cite
|
Sign up to set email alerts
|

Snakebites notified to the poison control center of Morocco between 2009 and 2013

Abstract: BackgroundSnakebites cause considerable death and injury throughout the globe, particularly in tropical regions, and pose an important yet neglected threat to public health. In 2008, the Centre Anti Poison et de Parmacovigilance du Maroc (CAPM) started to set up a specific strategy for the control of snakebites that was formalized in 2012. The aim of the present study is to describe and update the epidemiological characteristics of snakebites notified to CAPM between 2009 and 2013.MethodsThis retrospective fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
4
14
0
Order By: Relevance
“…We consistently found that young to middle-aged men (age group = 15-44 years) were most at risk of snakebites, corroborating similar findings from Ghana [22, 23, 24], other parts of West Africa [15, 25, 26, 27, 44, 46, 47] and Africa in general [30, 34, 48, 49, 50]. Adolescent and young men in their twenties are among the most active and adventurous, albeit least cautious, section of rural African people [24, 27, 44, 51].…”
Section: Discussionsupporting
confidence: 85%
“…We consistently found that young to middle-aged men (age group = 15-44 years) were most at risk of snakebites, corroborating similar findings from Ghana [22, 23, 24], other parts of West Africa [15, 25, 26, 27, 44, 46, 47] and Africa in general [30, 34, 48, 49, 50]. Adolescent and young men in their twenties are among the most active and adventurous, albeit least cautious, section of rural African people [24, 27, 44, 51].…”
Section: Discussionsupporting
confidence: 85%
“…According to the study of Chafi q, et al, the majority of victims were young, with a mean age of 26.8±17.2 years and a male/female sex ratio of 1.67 [7]. The highest annual incidence was observed in the region of Tangier-Tetouan followed by the region of Meknes-Tafi lalet.…”
Section: Epidemiology Of Snakebites In Moroccomentioning
confidence: 98%
“…This region is known to be agricultural and has a large population, a diverse fauna of snakes and a semiarid to arid climate. Regarding mortality, the studies of both Chafi q, et al, and Arfaoui, et al, revealed that the current annual mortality rate from snakebites reaches 3.9% [5,7], while a retrospective study between 1980 and 2008 revealed a higher rate of 7.2% [7]. The studies also showed that females aged more than 60 and less than 20 present a signifi cantly higher specifi c lethality [5].…”
Section: Epidemiology Of Snakebites In Moroccomentioning
confidence: 99%
See 1 more Smart Citation
“…Haemolysis, coagulopathy and AKI have also been observed 22. The blunt-nosed viper ( Macrovipera lebetina ) and the Moorish viper ( Macrovipera mauritanica ), the most common cause of snakebite in Morocco,23 are larger snakes, reaching 100–180 cm in length, greyish or reddish brown, with distinctive dorsal markings. Bites result in local envenoming and coagulopathy.…”
Section: Venomous Snakes In Africa and Europementioning
confidence: 99%